Supplemental effects of Haematococcus pluvialis in a low-fish meal diet for Litopenaeus vannamei at varying temperatures: growth performance, innate immunity and gut bacterial community - Lin, Sihan; Chen, Mengdie; Chen, Xuanqi; Li, Yanmei; Liu, Yafeng; Zhang, Peinan; Hou, Xiangyan; Tan, Beiping; Niu, Jin (Frontiers in Immunology, 2024)
This study examined the effects of Haematococcus pluvialis on the growth performance, innate immunity, and gut microbiota of Litopenaeus vannamei under different water temperature conditions. Feeding regimens included a 20% fishmeal diet (control), a low-fish meal (LFM) diet with 10% fishmeal and an LFM diet supplemented with 0.03% H. pluvialis. These diets were administered to six groups of L. vannamei at normal (30°C) (NT) and low (20°C) (LT) temperatures (NT_C, NT_LFM, NT_LFM_HP, LT_C, LT_LFM, and LT_LFM_HP) over 8 weeks. The weight gain rate of L. vannamei in group NT_LFM_HP was significantly higher compared to group NT_LFM. Astaxanthin levels and body pigmentation intensity in L. vannamei were significantly increased in the NT_LFM_HP and LT_LFM_HP groups. Moreover, hepatopancreatic antioxidant capacities, such as superoxide dismutase (SOD) activity and total antioxidant capacity (T-AOC), were lower in normal-temperature groups compared to the low-temperature groups. Nevertheless, antioxidant capacity was significantly higher in both the NT_LFM_HP and LT_LFM_HP groups compared to the control group. Meanwhile, the expression levels of antioxidants were significantly higher at lower temperatures compared to higher temperatures, with the NT_LFM_HP and LT_LFM_HP groups exhibiting the highest expression levels. Additionally, the mRNA levels of genes associated with the Toll and IMD pathways indicated immunoregulatory effects in the organism. The expression levels of immune genes were significantly higher at lower temperatures, especially in the NT_LFM_HP and LT_LFM_HP groups compared to the control groups. Notably, significant differences in gut microbial composition were observed in the NT_LFM_HP group compared to other groups, with variations influenced by temperature and fishmeal content. Specifically, Vibrionaceae abundance was significantly lower in the LT_LFM_HP group compared to the control group. The results also revealed that the abundance of Actinomarinales was significantly higher in low-temperature groups, with the LT_LFM_HP group displaying the greatest increase. Overall, these findings suggest that L. vannamei may be susceptible to reduced fishmeal levels, potentially impacting growth and immune function. Furthermore, H. pluvialis supplementation may assist L. vannamei in acclimating to prolonged low-temperature conditions.